Developing an emergency medicine handoff tool: an electronic Delphi approach - Khaled Alrajhi; Abdulmohsen Alsaawi (International Journal of Emergency Medicine, 2019)
Abstract Background Handoffs at the end of clinical shifts occur with high frequencies in the emergency department setting and they pose an increased risk to patients. There is a need to standardize handoff practices. This study aimed to use an electronic Delphi method to identify the core elements essential for an emergency department physician to physician handoff and propose a framework for implementation. Methods An electronic Delphi-style study with a national panel of board-certified emergency physicians in Saudi Arabia. The panel was conducted over four rounds. The first to identify elements relevant to the end of shift handoff and categorize them into domains, while the remaining three to score and debate individual elements. Results Twenty-five board-certified emergency physicians from various cities and practice settings were enrolled. All panelists completed the entire Delphi process. Thirty-two elements were identified and classified into 4 domains. The top five rated handoff elements were patient identification, chief complaint history, clinical stability, working diagnosis, and consulting services involved. Panel scores showed convergence as rounds progressed and the final list of elements had a high-reliability score (Cronbach’s alpha 0.93). Conclusions This study yielded an itemized and ranked list of elements that are easy to implement and could be used to standardize patient handoffs by emergency physicians. While this study was conducted on an emergency medicine panel, the methods used may be adapted to develop standardized handoff frameworks that serve different disciplines or practice settings.